Coins of Tokharistan with old Turkic titles - Babayarov, Gaibulla; Asanov, Eldar (Turkic Studies Journal, 2021)
The tamga signs and titles engraved on coins represent symbols of ruling dynasties and the states they had founded and were associated both with the territory where they ruled, as well as with their origin (ethnicity). In this regard of particular interest are Old Turkic tamgas and titles (“Qaghan”, “Yabghu” (?), “Tegin”, “Tarkhan”) available on the pre-Islamic Turkic coins of Tokharistan region (Southern Uzbekistan – Southern Tadjikistan – Northern Afghanistan) with Sogdian scripts. On the early medieval coins of Chach related to the Western Turkic Qaghanate (568-740), there are four types of tamgas – a lyre-shaped one with its varieties, a tamga in the form of two crossed swords, an anchor-form tamga and the diamond-form one, and the fact comes under notice that similar tamgas were engraved on the coins of the Northern Tokharistan of the epoch. Appearance of these tamgas and titles in the territory of Chach and Tokharistan in the Early Middle Ages is directly related to political activities of the Western Turkic Qaghanate and ethno-cultural processes which were taking place in Central Asia.